Pola Komunikasi Jarak Jauh dalam Menjaga Keharmonisan Keluarga pada Orang Tua dan Anak - Fauzan Yusuf, Muhammad Farraz; Yanti Tayo; Utami Dewi , Wahyu (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
The ever-evolving times will influence every family for family members to become smart individuals. Therefore, many parents want to provide the best education for their children. This research uses a qualitative method with the theory used in this research, namely interpersonal communication theory. The subjects in this study amounted to five resource persons selected based on certain criteria, namely parents and sons. The data collection techniques used were in-depth interviews, observation, and literature study. The purpose of this study is to determine the application and perception of long-distance communication patterns between parents and children in maintaining harmony. The results of the study state that there are several communication patterns that are established when long distance certainly raises concerns for both children and parents. However, with adequate facilities, it is easier for parents and children to communicate quickly even though they are far away. When long-distance communication is well established, it will create family harmony.